Algevir: An Expression System for Microalgae Based on Viral Vectors - Bañuelos-Hernández, Bernardo; Monreal-Escalante, Elizabeth; González-Ortega, Omar; Angulo, Carlos; Rosales-Mendoza, Sergio (Frontiers in Microbiology, 2017)
The use of recombinant algae for the production of valuable compounds is opening promising biotechnological applications. However, the development of efficient expression approaches is still needed to expand the exploitation of microalgae in biotechnology. Herein, the concept of using viral expression vectors in microalgae was explored for the first time. An inducible geminiviral vector leading to Rep-mediated replication of the expression cassette allowed the production of antigenic proteins at high levels. This system, called Algevir, allows the production of complex viral proteins (GP1 from Zaire ebolavirus) and bacterial toxin subunits (B subunit of the heat-labile Escherichia coli enterotoxin), which retained their antigenic activity. The highest achieved yield was 1.25 mg/g fresh biomass (6 mg/L of culture), which was attained 3 days after transformation. The Algevir system allows for a fast and efficient production of recombinant proteins, overcoming the difficulties imposed by the low yields and unstable expression patterns frequently observed in stably transformed microalgae at the nuclear level; as well as the toxicity of some target proteins.